2006
DOI: 10.1021/jf062740i
|View full text |Cite
|
Sign up to set email alerts
|

Andean Potato Cultivars (Solanum tuberosumL.) as a Source of Antioxidant and Mineral Micronutrients

Abstract: Potato tubers were evaluated as a source of antioxidants and minerals for the human diet. A genetically diverse sample of Solanum tuberosum L. cultivars native to the Andes of South America was obtained from a collection of nearly 1000 genotypes using microsatellite markers. This size-manageable collection of 74 landraces, representing at best the genetic diversity among potato germplasm, was analyzed for iron, zinc, calcium, total phenolic, total carotenoid, and total vitamin C contents. The hydrophilic antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
215
8
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(262 citation statements)
references
References 45 publications
34
215
8
5
Order By: Relevance
“…Yellow-orange pigmented potatoes usually have high carotenoid contents, such as lutein, zeaxanthin, violaxanthin, and antheraxanthin (Brown, 2005;Andre et al, 2007). They are present in different proportions depending on the genotype and on storage conditions.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Yellow-orange pigmented potatoes usually have high carotenoid contents, such as lutein, zeaxanthin, violaxanthin, and antheraxanthin (Brown, 2005;Andre et al, 2007). They are present in different proportions depending on the genotype and on storage conditions.…”
Section: Researchmentioning
confidence: 99%
“…The presence of these metabolites suggests that purple-and red-fleshed potatoes can be natural colorants or antioxidant sources for the food industry; however, a rigorous selection of genotypes with high antioxidant levels is needed. Phenolic acids, mainly chlorogenic acids, can consist of up to 90% of the total polyphenol content Shepody 192 ± 26a 565 ± 80a 29.39 ± 0.98fg Desirée 302 ± 31b 665 ± 63a 22.06 ± 1.52ab 457- CON-1157 (-) 191 ± 25a 630 ± 72a 33.06 ± 0.70h 254-CON-902 (Corazón de buey) 409 ± 41c 1248 ± 134bc 30.50 ± 0.55g 302-UA-1634A (-) 465 ± 56cd 1221 ± 161bc 26.26 ± 0.53cde 304- UA-1135 (-) 487 ± 34d 1177 ± 103b 24.15 ± 0.63bc 267-UA-1550 (Boyo de chancho) 506 ± 40de 1241 ± 112bc 24.53 ± 0.51cd 529 ± 36de 1365 ± 104c 25.81 ± 0.83cde NG-71 (Meca de gato) 563 ± 61ef 1564 ± 178d 27.71 ± 0.65def 283-UA-1108 (Cacho azul) 629 ± 65fg 1304 ± 108bc 20.81 ± 1.19a 301-UA-1500 (Corazón azul) 668 ± 64gh 1708 ± 144d 25.59 ± 0.78cd 239- UA-1388 (-) 733 ± 85h 2045 ± 186e 27.99 ± 1.28ef NG-5 (Chona negra) 945 ± 88i 2560 ± 270f 27.07 ± 1.16f 1864 ± 129j 4757 ± 273g 25.55 ± 0.83g in potatoes (Andre et al, 2007). Phenolic compounds are mostly distributed between the potato cortex and skin (peel) tissues (Friedman, 1997).…”
Section: Researchmentioning
confidence: 99%
“…Andean potatoes provide another rich and varied source of carotenoids. André et al (2007a) reported a range of 3 to 36 mg/kg DW for total carotenoids among 74 Andean landraces. In another study, André et al (2007b) screened 24 Andean cultivars and identified genotypes containing high concentration of lutein (1.12-17.7 mg/kg DW), zeaxanthin (18 mg/kg DW), and β-carotene (2 mg/kg DW).…”
Section: Factors Influencing Carotenoid Content In Tubersmentioning
confidence: 99%
“…It is also proposed to play a major role in the etiology and/or treatment of various chronic diseases such as sickle cell anemia, asthma, and cancer (Kolasa et al, 1993). Potato tubers are also important sources of minerals including phosphorous, calcium, zinc, potassium, and iron and their value in the human diet is often understated or ignored, particularly as a source of ascorbic acid (Dale et al, 2003;Yilmaz et al, 2005;Andre et al, 2007). Potato has shown a steadily growth rate over other main crops in developing countries (CIP, 2008) and remains an important role in the food security, nutrition and combating hunger (FAO, 2013).…”
Section: Introductionmentioning
confidence: 99%